The Eastern German Growth Trap: Structural Limits to Convergence? - Ulrich Blum (Intereconomics, 2019)
After an initial take-off during the first eight years following unification, the Eastern German economy started to stall and regress to its old growth path of the 1950s and 1960s. The initial quick convergence only compensated for the dismal stagnation that the expropriation and concentration strategies of party leader and general secretary Erich Honecker had produced. Since then, Eastern Germany has followed a two-thirds growth path compared to Western Germany, which shows that the structural problems of communist rule have not been overcome. The share of small and medium-sized firms is too small, creating an extremely fragmented group structure of firms and, thus, a lack of internationally active headquarters. A 1% increase of small and medium-sized firms on average reduces growth by 0.3%. This paper argues that catching up with the West will take more than a generation and needs to address central economic woes by encouraging endogenous, as well as exogenous growth through a merger-and-acquisition strategy and through the establishment of headquarters.
Keywords: 330